Fluctuating bail-in expectations and effects on market discipline, risk-taking and cost of capital - Raffaele Giuliana (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2022)
Through the compulsory participation of junior investors in bearing losses of their failing bank, the bailin attempts to limit bail-outs' side-effects in terms of market discipline, too-big-to-fail, bank-sovereign nexus and risk-taking. This paper assesses the consequences of bail-in expectations along these dimensions ensuring - through a bond pricing study - that bail-in expectations are not confounded by other factors. Using hand-collected details of EU bail-in events, I study both positive and negative exogenous shocks to bail-in expectations, offering three sets of findings. First, bail-in events can reinforce (or weaken) bail-in expectations, as shown by Khwaja-Mian tests (validated by placebo analyses). Second, bail-in expectations promote market discipline, and mitigate too-big-to-fail and banksovereign nexus. Third, bail-in effects on bank resilience appear mixed. While it incentivises banks to reduce risk-taking (e.g., increasing risk-weighted equity by a third of Basel III requirement), it also remarkably exacerbates total funding costs through an increase in equity cost (partially off-set by a debt cost reduction).
Keywords: G21; G28; H81; C23; 330; Bail-in; Fixed-income Claims; Expectations; Rating; Market Discipline; Risk-taking; Cost of Capital; Financial Stability